Low-energy broad area electron beam for etching microelectronic materials - Rocca, Jorge J., author; Verhey, T. R., author; Boyer, P. K., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1987)
We have generated beams with electron current densities of more than 10 mA/cm2 at energies between 150 and 900 eV using a plasma source. This electron source can be operated at background pressures between 0.01 and 0.1 Torr in helium and with the addition of various gases, producing electron beams up to 3.8 cm in diameter. The broad area beam can be used to induce gas phase and surface reactions and has been successfully used to achieve anisotropic etching of SiO2 films in the reactant gas CF4.